Did Community Rating Induce an Adverse Selection Death Spiral? Evidence from New York, Pennsylvania, and Connecticut - Buchmueller, Thomas; DiNardo, John (American Economic Review, 2002)
Did Community Rating Induce an Adverse Selection Death Spiral? Evidence from New York, Pennsylvania, and Connecticut by Thomas Buchmueller and John Dinardo. Published in volume 92, issue 1, pages 280-294 of American Economic Review, March 2002